2004
DOI: 10.1111/j.0022-4537.2004.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Children of the Troubles: The Impact of Political Violence in Northern Ireland

Abstract: This article explores the effects of political violence on children and young people in Northern Ireland. The article begins with a brief historical account of the Northern Irish conflict and the recently negotiated Belfast Good Friday Agreement of 1998. This account illustrates, as is the case with many conflicts, its basis is religious, national, economic, and political, despite its frequent construction as a battle between Protestant and Roman Catholic. The article goes on to review young peoples' experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 49 publications
(73 reference statements)
1
56
0
Order By: Relevance
“…In addition, in cases of evident pathology, symptomatology has been inconsistent across studies ranging from symptoms such as anger and other externalizing behaviors (Barber 2001;Muldoon 2004), depression (Barber 2001) to PTSD (Masinda and Muhesi 2004). This corpus of research questions earlier assumptions of automatic severe impairment and indicates the complexity of determining effects of political violence on youth.…”
Section: Effects Of Political Violence and Conflict On Youthmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, in cases of evident pathology, symptomatology has been inconsistent across studies ranging from symptoms such as anger and other externalizing behaviors (Barber 2001;Muldoon 2004), depression (Barber 2001) to PTSD (Masinda and Muhesi 2004). This corpus of research questions earlier assumptions of automatic severe impairment and indicates the complexity of determining effects of political violence on youth.…”
Section: Effects Of Political Violence and Conflict On Youthmentioning
confidence: 95%
“…On the side demonstrating damaging consequences, studies have indicated that exposure to war and political violence frequently leads to developmental impairment and psychiatric symptomatology, ranging from isolated symptoms to profiles of disorder (Allwood et al 2002;Dyregrov et al 2000;Muldoon 2004;Thabet et al 2002). On the opposite side of the continuum is evidence suggesting that children who grow up in politically violent environments may exhibit surprising resilience and successful adjustment (Barber 2009).…”
Section: Effects Of Political Violence and Conflict On Youthmentioning
confidence: 99%
“…In summarizing the protracted period since the eruption of violence, Muldoon (2004) notes '[f]or close to three decades, violence between and within paramilitary groups has proliferated and heavily armed police and soldiers patrolled the streets of Northern Ireland. Though the violence has varied in form and intensity over this time, it can generally be characterized as low intensity urban guerrilla warfare.…”
Section: Historical and Sociocultural Context Of Northern Irelandmentioning
confidence: 99%
“…For example, violence has been unevenly distributed across Northern Ireland (Muldoon, 2004;Smyth & Hamilton, 2003;Trew, 2004), with working class neighbourhoods, especially in urban areas, being disproportionately affected (Fay et al, 1999). Those living in high violence areas have been shown to experience greater levels of psychiatric distress than those in low violence areas, especially if they perceive their area as violent and dangerous (Cairns & Wilson, 1984).…”
Section: Historical and Sociocultural Context Of Northern Irelandmentioning
confidence: 99%
“…In a post-conflict society of such dualities, the violent outworking of continued division is not unprecedented. Peacetime violence in all its forms: sectarian, political, racist, informal, domestic and 'everyday' in Northern Ireland remains a formidable challenge (McAlister et al, 2013;Feldman 1991;Muldoon 2004). …”
Section: Introductionmentioning
confidence: 99%